Rancang Bangun Alat Pengukur Dan perhitungan Energi Listrik Menggunakan ACS 712 Berbasis Arduino - Imam Ahmad Tarigan; Agus Almi Nasution (Jurnal Simetri Rekayasa, 2021)
Electrical energy is one of the quantities of energy in the form of electricity that is used to carry out a business, for example to turn on lights, cool a room, heat water, cook and so on. Electrical energy is rarely measured or calculated so it is rarely known how much electrical energy has been used. Generally, there are only measuring instruments for measuring voltages and currents or amperes. Energy is the product of current, voltage and time or power multiplied by time. The only energy measurement tool is the PLN kwh meter. However, the kwh meter is difficult to monitor because it is accumulative and cannot be reset to 0. So it is difficult to use it as a measure of electrical energy. This design uses Arduino Uno 328 to process the input signal from the voltage sensor and the ACS 712 sensor. The voltage sensor functions as to measure voltage. and the ACS 712 sensor serves to measure current. Then the results of the measurement data and calculations can be viewed on the LCD. LCD as output from Arduino Uno